Analisis Kedisiplinan Kerja Karyawan Pada Kedai Kopi C+C Coffee Berdasarkan Undang-Undang Nomor 13 Tahun 2003 - Mikael, Raykrisanda; Santosa, Anak Agung Gede Duwira Hadi (CV. Lenggogeni Data Publishing, 2026)
Abstract The purpose of this journal is to find out what obstacles, sanctions, and efforts that can be given in efforts to implement employee work discipline at C + C Coffee Shop. Thus, the problem formulation raised in this journal is what obstacles arise in efforts to implement employee work discipline at C + C Coffee Shop and what sanctions and efforts can be given to C + C Coffee Shop employees who violate the work agreement. The study methodology used in this legal discipline, which is usually referred to as